(untitled) (Historia, 2021)
Archaeology is the technique of the study of old things made by man or related to man’s activities from man’s origin to the present day. The technique archaeology may be applied to develop hypotheses related to human activity or the process of change in human activity before the appearance of written documentation. Hypotheses developed prior to written documentation are known as prehistory and hypotheses developed after written documentation are known as history. In the South African context all human activity prior to White settlement is prehistoric. The border between prehistoric and historic South Africa moved inland with White penetration of the South African interior. By AD1823 the South-Western Transvaal was within the historic record. Prehistoric archaeology in the South African interior is concerned with the study of human activity from its earliest beginnings to the local beginnings of written records. Historic archaeology starts when prehistoric archaeology fades, commencing in the South-West Cape circa AD1497 and in the Transvaal circa AD1823. Today South Africa, the world and its satellite are within the realm of historic archaeology. Historic archaeology in South Africa supplements written history. The archaeologist identifies localities and artefacts associated with historically recorded events or on the fringes of these events.